Prognostic factors in children with extracranial germ cell tumors treated with cisplatin-based chemotherapy - Jinsup Kim; Na Hee Lee; Soo Hyun Lee; Keon Hee Yoo; Ki Woong Sung; Hong Hoe Koo; Jeong-Meen Seo; Suk-Koo Lee (Korean Pediatric Society, 2015)
PurposeTo evaluate the outcomes and prognostic factors in children with extracranial germ cell tumors (GCTs) treated at a single institution.MethodsSixty-six children diagnosed with extracranial GCTs between 1996 and 2012 were included in the study. Primary treatment was surgical excision, followed by six cycles of cisplatin-based chemotherapy. The survival rates were compared according to the International Germ Cell Cancer Cooperative Group classification used for GCTs in adults to validate the classification guidelines for GCTs in children.ResultsThe median patient age was 4.4 years. In 34 patients (51.5%), the primary tumor site was the gonad. Extragonadal GCTs were detected in 32 patients. The 5-year overall survival and event-free survival (EFS) were 92.0%±3.5% and 90.4%±3.7%, respectively. In univariate analysis, tumor histology, metastasis, and elevated alpha-fetoprotein were not prognostic factors in children with extracranial GCTs. However, EFS was poorer in patients with mediastinal disease (n=12, 66.7%±13.6 %) than in those with nonmediastinal disease (n=54, 96.0%±2.8%) (P=0.001). The 5-year EFS was lower in patients older than 10 years, (n=21, 80.0%±8.9%) compared with those younger than 10 years (n=45, 95.2%±3.3%) (P=0.04). Multivariate analysis identified the mediastinal tumor site as the only independent prognostic factor.ConclusionThe prognosis of children with extracranial GCTs was favorable. However, nongerminomatous mediastinal tumors were associated with poor survival in children. Further research is needed to improve the prognosis of children with malignant mediastinal GCTs.